Conversações entre Cibernética e Alquimia: distinção, diálogo e emergência - Diego Fagundes da Silva (2021)
This thesis presents and discusses Alchemy and Cybernetics as fields in interaction, even if separated by an extensive interval of time. Both are, from a constructivist perspective, models for structuring the world and collective communication systems within particular cultural processes. From an experimental basis, Alchemy deals with transformation processes, mirrored both in an understanding of the dynamics of nature and in the recursive bond between mind, matter and universe. Cybernetics, like Alchemy, arises from an interdisciplinary view of knowledge associated with a specific historical and technological context, being, since its origin, the field that assimilates and operationalizes complexity and unpredictability in mechanical, biological and social systems. The analysis developed in this research departs from a specific understanding of each field and from the contraposition of concepts present in both - with emphasis on the notions of distinction, dialogue and emergence - in addition to the elaboration of imagery studies capable of revealing some of the essential and implicit aspects of this relationship. Thus, it is possible to formalize a conversation model with the objective of making such discoveries concrete and enabling future conceptual developments. The proposed model assumes the geometric contour of an ellipse that - being an eccentric shape with two convergence points - simultaneously maintains the autonomy of the two fields and, by encapsulation, produces an entirely new entity.